Autoclave foaming of chemically modified polylactide. (September 2017) - Standau, Tobias; Goettermann, Svenja; Weinmann, Sandra; Bonten, Christian; Altstädt, Volker
Polylactide has emerged as one of the most promising biopolymers due to its good mechanical properties, as reflected by the continual increase in its production volume per year. However, one of the main drawbacks of polylactide is its low melt strength, which is disadvantageous in terms of foaming. To overcome this issue, in this study, several chemical modifiers that induce crosslinking, chain extension or grafting were incorporated by reactive extrusion, which greatly affected the foaming process by increasing the molecular weight and thereby the melt properties of polylactide. By means of gel permeation chromatography, an increase in the molecular weight was observed in the modified polylactides. Elongational viscosity measurements indicate a dramatic viscosity increase for polylactide modified with a multifunctional epoxide and an organic peroxide. With pressure-induced batch foaming, almost all modifications, with the exception of styrene maleic anhydride, led to a decrease in foam density compared to the neat polylactide.